THE INFLUENCE OF WEBSITE QUALITY, PRICE, AND SERVICE QUALITY ON CUSTOMER SATISFACTION OF TOKOPEDIA E- COMMERCE (CASE STUDY ON STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, MALIKUSSALEH UNIVERSITY) - Fitri Faryani Manik; Halida Bahri; Ikramuddin; T. Edyansyah (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of website quality, price, and service quality on customer satisfaction with e-commerce Tokopedia, with a case study on students of the Faculty of Economics and Business, Malikussaleh University. The research method used is a quantitative approach with purposive sampling technique involving 120 respondents. Data was collected through questionnaires and analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination (R²). The results indicate that partially, website quality, price, and service quality have a positive and significant influence on customer satisfaction. Simultaneously, these three variables also have a significant effect on customer satisfaction, with a coefficient of determination value of 72.3%. These findings suggest that good website quality, competitive pricing, and satisfactory service are key factors in enhancing customer satisfaction with Tokopedia.